Lack and Desire in the Pursuit of an Ideal Life in The Midnight Library by Matt Haig - Vebyana Putri Amanda; Karina Hanum Luthfia (Universitas Cokroaminoto Palopo, 2026)
In The Midnight Library, Nora Seed experiences feelings of regret, emptiness, and dissatisfaction with her life, leading her to continuously imagine alternative lives perceived as more perfect. This study aims to analyze the manifestation of Jacques Lacan’s concepts of lack and desire in Nora’s life journey and to reveal the novel’s critique of the ideal life standards within modern middle-class society. This study employs a qualitative descriptive method using a Lacanian psychoanalytic approach. The data are obtained from dialogues, narratives, and events that represent the psychological conflicts experienced by the main character. The findings reveal that lack is manifested through feelings of emptiness and incompleteness that give rise to desire for various alternative lives. However, every life experienced by Nora ultimately fails to provide complete satisfaction because desire continuously shifts and can never be fully fulfilled. Thus, the concepts of lack and desire in the novel not only portray Nora’s psychological condition, but also function as a critique of the illusion of an ideal life within modern society.